Gender, Violence, and Migration in Conflict-Affected Communities: An Ecocritical and Literary Reading of Djaïli Amadou Amal’s Coeur du Sahel - ISIAQ, Aishat Olayetunde; SOULEYMANE, Alani (dialektika kontemporer, 2025)
While scientific studies have extensively documented the impacts of insurgency and environmental degradation through data on malnutrition, displacement, and mortality, a critical gap remains in understanding their profound human and emotional toll, particularly on women and girls. Moving beyond statistics, this study argues that literature provides an essential humanistic lens for grappling with these lived realities. Through a multidisciplinary feminist framework combining decolonial psycho-feminism, ecofeminism, trauma theory, and intersectionality, this paper analyses Djaïli Amadou Amal’s novel Cœur du Sahel as a narrative that reflects the socio-emotional consequences of conflict and ecological collapse in Sahelian and Northern Nigerian communities. The analysis demonstrates how these intersecting crises catalyse systemic gendered exploitation, forced migration, and the deep internalisation of trauma. Crucially, however, it also reveals how the novel foregrounds resistance, reimagining education and solidarity as subversive strategies for reclaiming agency. Ultimately, this paper contends that Cœur du Sahel transcends its literary form to function as a vital work of feminist testimony, transforming individual suffering into collective memory and advocating for the dignity of girls in conflict-affected regions.